The meaning of work and sense of calling for students in nanyang business school. - Kang, Zhijue. (2013)
Research has consistently highlighted the importance of meaning of work. Therefore, this study applies some of these theories and concepts in determining meaningful work for students in Nanyang Business School (“NBS”) in particular. It adopts a qualitative grounded approach to identify a set of fourteen themes that reflected the meaning of work to NBS students. Students were found to describe meaning of work themes in terms of achievement and autonomy/growth striving more than communion and status striving.